Factores traumáticos y fobia especifica en una estudiante de 9 años - Miranda Bravo, Mixi Liseth (2019)
People with Specific Phobia try hard to escape and avoid what they fear. When they are forced to face each other, they do it with much discomfort, they are determined by various aspects of action and interaction in social situations, the components of fear and avoidance becoming important. Different evolutionary, familiar, environmental, evolutionary, temperamental, neurobiological, genetic, biological, psychological and sociocultural factors are associated with this disorder, reflecting its great complexity. The acquisition of fear is caused by experiencing a traumatic situation or having witnessed a traumatic experience of another person. The objective of this theoretical study is to show a description of the way in which these factors are associated with the specific phobia, as well as the main studies related to it. What will empower essential tools for the comprehensive approach and diagnosis of Simple or Specific Phobia